Transintestinal transport of the anti-inflammatory drug 4F and the modulation of transintestinal cholesterol efflux[S] - Meriwether, David; Sulaiman, Dawoud; Wagner, Alan; Grijalva, Victor; Kaji, Izumi; Williams, Kevin J.; Yu, Liqing; Fogelman, Spencer; Volpe, Carmen; Bensinger, Steven J.; Anantharamaiah, G.M.; Shechter, Ishaiahu; et al. (Journal of lipid research, 2016)
The site and mechanism of action of the apoA-I mimetic peptide 4F are incompletely understood. Transintestinal cholesterol efflux (TICE) is a process involved in the clearance of excess cholesterol from the body. While TICE is responsible for at least 30% of the clearance of neutral sterols from the circulation into the intestinal lumen, few pharmacological agents have been identified that modulate this pathway. We show first that circulating 4F selectively targets the small intestine (SI) and that it is predominantly transported into the intestinal lumen. This transport of 4F into the SI lumen is transintestinal in nature, and it is modulated by TICE. We also show that circulating 4F increases reverse cholesterol transport from macrophages and cholesterol efflux from lipoproteins via the TICE pathway. We identify the cause of this modulation of TICE either as 4F being a cholesterol acceptor with respect to enterocytes, from which 4F enhances cholesterol efflux, or as 4F being an intestinal chaperone with respect to TICE. Our results assign a novel role for 4F as a modulator of the TICE pathway and suggest that the anti-inflammatory functions of 4F may be a partial consequence of the codependent intestinal transport of both 4F and cholesterol.